Non-coding RNAs in the vasculature - Thum, Thomas; Dimmeler, Stefanie (Springer, 2017)
This book focuses on the importance of regulatory RNAs in the vasculature. The main topics discussed include the role of regRNAs in vascular development and angiogenesis, ischemic cardiovascular disease and repair mechanisms, diabetic and metabolic vascular disease, atherosclerosis and vascular inflammation, as well as diagnostics of vascular disease using circulating miRNAs. Lastly, it offers an overview of emerging topics such as microvesicle-mediated miRNA cellular trafficking and the vascular importance of long non-coding RNAs. It is an invaluable resource for academics, researchers and students working in the field of vascular biology.
Keywords: Non-coding RNA.; elektronické knihy; electronic books